Rage against the Machine: Vincenzo Agnetti’s Critique of Industrial Alienation (ENTHYMEMA, 2012)
This essay analyzes the work of the Milanese artist Vincenzo Agnetti (1926-1981), in particular his pieces La macchina drogata (1968) and NEG (1970). Like other Italian artists and intellectuals of the 1960s and 1970s, Agnetti was concerned about the alienation caused by industrial development and consumer society, manifested in carefully designed objects of everyday use. To counteract the automatism of perception and thought that he considered the sign of alienated experience, Agnetti’s artworks employed several strategies that obliged the public to attend to its thinking processes. Thus, Agnetti put in practice forms of aesthetic estrangement similar to those evoked in the same period by Gillo Dorfles and Umberto Eco to counteract the widespread loss of awareness.
Keywords: Estrangement; Industrial Design; Conceptual art; Zeroing